Targeting the plasticity of intestinal neutrophils: bidirectional regulation strategies by natural products - Kang, Ruotong; Sun, Anqi; Yang, Jiayin; Chang, Linyuan; Sun, Wenguang; Kou, Fushun; Cheng, Yuan (Frontiers in Immunology, 2026)
Historically, neutrophils have been regarded primarily as pro-inflammatory cells, yet recent advancements have revealed their phenotypic heterogeneity and functional plasticity with versatile immunophenotypes. Distinct subpopulations of neutrophils exhibit a functional duality, not only initiating and amplifying inflammation, but also actively promoting tissue restoration in diseases, such as inflammatory bowel disease (IBD), colorectal cancer (CRC) and intestinal infections. They contribute to the formation of a dynamic immune microenvironment in concert with the intestinal microbiota, epithelial cells, and other immune cell types. Current first-line therapies for enteric diseases often lack precision in modulating neutrophil functions. In contrast, natural products including alkaloids, polysaccharides, polyphenols, quinones, and glycosides, as well as microbiota-derived metabolites, exhibit distinct advantages for ability to achieve multi-targeted and bidirectional immunomodulation. These compounds target neutrophil activation, migration, neutrophil extracellular trap formation, cytokine release, oxidative stress, and energy metabolism etc. In this review, we systematically examine the heterogeneity and functional diversity of intestinal neutrophils, highlighting their interaction mechanisms with the surrounding microenvironment. Potential of natural products to modulate neutrophil functions via multi-target strategies has not been fully explored. Moreover, the review discusses novel precision therapeutic approaches based on neutrophil nanotechnology and engineered cell drug delivery. These cutting-edge technologies aim to enhance natural products delivery to inflammatory sites, provide controllable regulation of neutrophil function, and facilitate the degradation of pathological structures. Collectively, the study presents new research directions and theoretical frameworks for intervention of natural products in neutrophils of intestinal immune-related disorders, notably IBD and even CRC.